Multiple ORC-binding sites are required for efficient MCM loading and origin firing in fission yeast - Takahashi, Tatsuro (Oxford University Press, 2003)
In most eukaryotes, replication origins are composed of long chromosome regions, and the exact sequences required for origin recognition complex (ORC) and minichromosome maintenance (MCM) complex association remain elusive. Here, we show that two stretches of adenine/thymine residues are collectively essential for a fission yeast chromosomal origin. Chromatin immunoprecipitation assays revealed that the ORC subunits are located within a 1 kb region of ori2004. Analyses of deletion derivatives of ori2004 showed that adenine stretches are required for ORC binding in vivo. Synergistic interaction between ORC and adenine stretches was observed. On the other hand, MCM subunits were localized preferentially to a region near the initiation site, which is distant from adenine stretches. This association was dependent on adenine stretches and stimulated by a non-adenine element. Our results suggest that association of multiple ORC molecules with a replication origin is required for efficient MCM loading and origin firing in fission yeast.